Fluoroscopy-assisted identification of the individual optimal antegrade entry point of the anterior column fixation corridor in pelvic and acetabular surgery: a novel perspective - Vedat ÖZTÜRK; Mustafa Gökhan BİLGİLİ (Journal of Orthopaedic Surgery and Research)
Abstract Introduction This study aims to describe a novel axial fluoroscopic imaging technique for visualizing the anterior column fixation corridor (ACFC) of the acetabulum in the supine position, define the patient-specific optimal antegrade entry point (OAEP), and evaluate the feasibility of screw placement using this approach. Materials and methods Pelvic computed tomography (CT) data from 500 healthy adults (250 men and 250 women) were collected. Using Fujifilm-Synapse 3D software, 3D reconstructions of the pelvis were created. Through fluoroscopy simulation, the axial view of the ACFC and OAEP was obtained for each individual. To simulate screw placement radiologically, a cylinder was placed through the OAEP, completely filling the corridor without protruding. The position was verified using both fluoroscopic simulations and three different CT sections (axial, coronal, sagittal). The corridor’s diameter (ACFC-R), length (ACFC-L), and the coronal plane inclination (CPI) and sagittal plane inclination (SPI) required for fluoroscopic visualization of the OAEP were measured in all pelvic models. Results The axial view and patient-specific optimal antegrade entry point (OAEP) of the fixation corridor were successfully visualized in all pelvises. Radiological virtual screw placement was successfully performed in all models by visualizing the OAEP, enabling precise axial screw insertion through the corridor. The average ACFC diameters were 6.2 mm in females and 8.6 mm in males (p < 0.001); ACFC lengths were 116.8 mm in females and 122.5 mm in males (p < 0.001). The SPI was 14.3 degrees in females and 14.7 degrees in males (p = 0.263). The CPI was 35.5 degrees in females and 33.2 degrees in males (p < 0.001). Except for the SPI, statistically significant differences were observed in all parameters between genders. Conclusion The axial fluoroscopic imaging technique enables accurate identification of patient-specific entry points and screw placement that fills the fixation corridor without boundary breach, potentially enhancing the precision and safety of anterior column fixation.